COMPARISON OF ORAL CLONIDINE WITH ORAL MIDAZOLAM IN MANAGING AGITATION FOLLOWING SEVOFLURANE ANESTHESIA – A PROSPECTIVE, RANDOMIZED, DOUBLE BLINDED STUDY - Charles S, Antony John; M S, Raghuraman; Sharma, Raji; Veliath, David George (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT: Objective: Emergence agitation is a major problem during recovery from anesthetic agents like sevoflurane, particularly in children. This study had compared the effects of oral clonidine with oral midazolam in reducing the incidence of emergence agitation following sevoflurane anesthesia. Methods: 50 children of ASA status I and II aged between 3-8 years were randomly allotted to one of the two groups, each group comprising 25 children. Group I children were given oral Midazolam 0.5 mg/kg and Group II children were given oral Clonidine 4 mcg/kg 30 min before the induction of anesthesia. Emergence reaction was analyzed using modified objective pain scale in all children following sevoflurane administration. Results: The total agitation score was significantly less in clonidine group in comparison to midazolam group during the first hour of post operative period (P<0.05).No remarkable change in the hemodynamics or oxygen saturation was observed in both groups. Conclusion: Premedication of oral clonidine 4 microgram per kg is superior to oral midazolam 0.5 mg per kg in reducing the incidence of emergence agitation following sevoflurane anesthesia. Keywords: sevoflurane, recovery, emergence agitation, clonidine, midazolam.